Some Important Food Quality Traits of Autochthonous Grape Cultivars - Muhammed Kupe; Sezai Ercisli; Neva Karatas; Sona Skrovankova; Jiri Mlcek; Monika Ondrasova; Lukas Snopek (Journal of Food Quality)
Grapes (Vitis L.), one of the most important and old fruit crops in the world, are grown in a wide range of environments from Australia to North America and from Japan to Chile. All grape growing countries use both international and local cultivars in production to obtain fresh and dried fruits or wine. In Turkey, each region has their own local grape cultivars. Seven local cultivars and one standard grape cultivar, grown in Coruh valley, were analyzed for morphological traits (bunch size, berry color, and berry shape), biochemical characteristics (sugars, organic acids, vitamin C, phenolic compounds, total carotenoids, and flavonoids content), and % inhibition level (antioxidant capacity). The grape cultivars differed from each other in the morphological and biochemical traits. The grape berries contain predominantly nine main phenolic compounds, five organic acids, and two sugars. Among phenolic compounds, chlorogenic acid, syringic acid, rutin, and quercetin were found to be dominant for most of the cultivars between 2.365–5.112 mg/L, 0.923–2.147 mg/L, 0.856–1.711 mg/L, and 0.621–1.347 mg/L, respectively. The local cultivar Kirmizi Istanbul had more chlorogenic acid than the other cultivars. The berries with darker skin color, specifically Kara Turfanda and Nanebur, had higher % inhibition level (antioxidant capacity) than the brighter ones, which correspond also to the results of flavonoid contents. Overall, the local genotypes were found promising due to favorable properties and could be recommended for farmers and consumers.